Impacts of mining projects on food security of households in Ethiopia: empirical evidence from Benishangul-Gumuz Region - Haile, Netsanet Zeleke; Huluka, Admassu Tesso; Beyene, Amsalu Bedemo (Frontiers in Sustainable Food Systems, 2024)
It's challenging to predict the potential impacts of mining extraction on household food security. On the one hand, mining projects can create job opportunities, improve market access, and enhance infrastructure. On the other hand, these projects can have adverse effects on livelihood assets, such as farmland, livestock, and grazing areas, which are crucial for household food security. The purpose of this article is to bridge the gap by studying impacts of mining projects on household food security in Ethiopia, using empirical evidence from the Benishangul-Gumuz Region (BGR). To achieve this goal, we employed a cross-sectional and quasi-experimental research designs. Using systematic random sampling, we collected primary data from a sample of 333 households, comprising 162 from a community located around the mining projects (treated households) and 171 from a community without mining projects in the area (control households). We analyzed the data using descriptive statistics and Propensity Score Matching (PSM) techniques. We measured food availability by assessing food energy intake (FEI). We evaluated food utilization by using the food consumption score (FCS), and we determined food stability through the coping strategy index (CSI). The Average Treatment Effect on the Treated (ATT) results show that treated households, on average, consume 1407.34 kcal per adult per day and 8.54 more FCS per week compared to control households, respectively. The ATT results also showed that treated households had a 3.24 lower CSI than control households. This is due to the wage employment created by small-scale and the infrastructure built by large-scale mining projects in the study area. Our research indicates that expanding mining investments brings benefits, as long as local sustainable development is taken into account.